The da vinci code - Brown, Dan (Corgi Books London, 2009)
The record-breaking bestseller A man is murdered in the world's most famous museum. Around his body is a ring of codes, drawn in blood. He died to protect a secret which Robert Langdon must uncover. It will be a race against time to decipher this final message. Can he get there before the killers do?